Blood urea nitrogen to creatinine ratio is associated with in-hospital mortality in critically ill patients with venous thromboembolism: a retrospective cohort study - Puri, Anju; Giri, Mohan; Huang, Huanhuan; Zhao, Qinghua (Frontiers in Cardiovascular Medicine, 2024)
The relationship between the blood urea nitrogen to creatinine ratio (BCR) and the risk of inhospital mortality among intensive care unit (ICU) patients diagnosed with venous thromboembolism (VTE) remains unclear. This study aimed to assess the relationship between BCR at admission upon admission to the ICU and in-hospital mortality in critically ill patients with VTE.This retrospective cohort study included patients diagnosed with VTE from the Medical Information Mart for Intensive Care IV (MIMIC-IV) database. The primary endpoint was inhospital mortality. Univariate and multivariate logistic regression analyses were conducted to evaluate the prognostic significance of the BCR. Receiver operating characteristic (ROC) curve analysis was utilized to determine the optimal cut-off value of BCR. Additionally, survival analysis using a Kaplan-Meier curve was performed.A total of 2560 patients were included, with a median age of 64.5 years, and 55.5% were male.Overall, the in-hospital mortality rate was 14.6%. The optimal cut-off value of the BCR for predicting in-hospital mortality in critically ill VTE patients was 26.84. The rate of in-hospital mortality among patients categorized in the high BCR group was significantly higher compared to those in the low BCR group (22.6% vs. 12.2%, P<0.001). The multivariable logistic regression analysis results indicated that, even after accounting for potential confounding factors, patients with elevated BCR demonstrated a notably increased in-hospital mortality rate compared to those with lower BCR levels (all P<0.05), regardless of the model used. Compared to patients in the low BCR group, those in the high BCR group had a 77.77% greater risk for in-hospital mortality [hazard ratio (HR): 1.7777; 95% CI: 1.4016-2.2547]. Patients in the high BCR group exhibited a 77.77% higher risk of in-hospital mortality than those in the low BCR group [hazard ratio (HR):1.7777; 95% CI: 1.4016-2.2547].An elevated BCR level was independently linked with an increased risk of in-hospital mortality among critically ill patients diagnosed with VTE. Given its widespread availability and ease of measurement, BCR could be a valuable tool for risk stratification and prognostic prediction in VTE patients.